The impact of macrophages on endothelial cells is potentiated by cycling hypoxia: Enhanced tumor inflammation and metastasis - Delprat, Victor; Huart, Camille; Feron, Olivier; Soncin, Fabrice; Michiels, Carine (Frontiers in Oncology, 2022)
In cancers, the interaction between macrophages and endothelial cells (ECs) regulates tumor inflammation and metastasis. These cells are both affected by cycling hypoxia (cyH), also called intermittent hypoxia, a feature of the tumor microenvironment. cyH is also known to favor tumor inflammation and metastasis. Nonetheless, the potential impact of cyH on the dialog between macrophages and ECs is still unknown. In this work, the effects of unpolarized, M1-like and M2-like macrophages exposed to normoxia, chronic hypoxia (chH) and cyH on endothelial adhesion molecule expression, pro-inflammatory gene expression and on EC adhesiveness for monocytes and cancer cells was investigated. CyH increased the ability of unpolarized and M1-like macrophages to induce EC inflammation and to increase the expression of the EC endothelial adhesion molecule ICAM1, respectively. Unpolarized, M1-like and M2-like macrophages were all able to promote EC adhesive properties toward cancer cells. Furthermore, the ability of macrophages (mostly M1-like) to shift EC phenotype towards one allowing cancer cell and monocyte adhesion onto ECs was potentiated by cyH. These effects were specific to cyH since they were not observed with chH. Altogether, these results show that cyH amplifies the effects of macrophages on ECs which may promote tumor inflammation and metastasis.